St Vincent and the Grenadines development plan 1986-1988 : growth, diversification, redistribution (Ministry of Finance and Planning. Central PlanningDivision KingstownVC, 1986)
Outlines the government's developmental objectives, strategies, policies, programmes, projects, and fiscal policy for the three year period 1986-88. Plans cover eleven sectors of the economy eg. agriculture, industry, public utilities, education, and social development. Describes the administrative organization for planning and plan implementation.
IDS